Governing Through Algorithms: Ethical and Legal Implications of Technological Governance - Miebaka Nabiebu; Ntamy Agube; Mokutima Etido Ekpo (Amicus Curiae: Journal of Law and Justice Dialogue, 2025)
This article examines a dilemma inherent in our reliance on new technologies that promise to improve legal governance's imperfections. On the one hand, there is widespread dissatisfaction with the current state of legal governance, which is often rooted in the inherently human nature of the legal system. Despite this, we remain emotionally and philosophically tied to the human-centred aspects of legal governance. On the other hand, we recognize the potential advantages that technological governance could bring, although this may come at the expense of reducing human involvement. Struggling between these two opposing forces, we try to preserve the human element by emphasizing that governance must respect human rights and dignity, or more specifically, that technology’s application should be constrained to maintain a human-centric approach. With the increasing demand for technology that serves human interests, we reflect on the extent to which humans should and could utilize new tools to improve the imperfections of legal governance. Should these tools merely assist human decision-making, or could they replace human involvement altogether? Or, might we eventually transition to a system of governance that relies on technological management of spaces, products, and processes, thereby reducing the need for human involvement and rule-based systems? In conclusion, it is critical that new technologies be carefully regulated in all areas of governance and across all human societies to prevent undermining the essential conditions that sustain viable human communities and their governance systems.